Challenges beyond F-Value, Water Activity and Glass Transition Concept in Determining Food Stability (Journal of Chemical Engineering, 2013)
Theoretical concepts of F-value, water activity and glass transition are the most successful in determining food stability during food processing and storage. The water activity and glass transition concepts are progressed by combining these concepts in a stability map named as state diagram. The first part of this paper provides stability criteria based on Fvalue, water activity, glass transition and state diagram. The second part explains the recently proposed macro-micro region concept in the state diagram. In this concept, 13 micro-regions are mapped and then relative stability criteria between the micro-regions are postulated. Final part presents real challenges in combing different hurdles in food preservation. DOI: http://dx.doi.org/10.3329/jce.v27i1.15858 Journal of Chemical Engineering, IEB Vol. ChE. 27, No. 1, June 2012: 48-52